Treatment with brivaracetam has no apparent long‐term effects on body weight in pediatric patients with epilepsy - Florin I. Floricel; Paula E. Reichel; Najla Dickson; Sofia Fleyshman; Christoph Reichel; Jan‐Peer Elshoff (Epilepsia Open)
Abstract Objective The objective of this study is to evaluate possible long‐term effects of treatment with brivaracetam (BRV) on body weight in children with epilepsy. Method Post hoc analysis of data from patients (aged 1 month to <17 years) with ≥6 months of BRV treatment in a long‐term, open‐label trial (N01266 [NCT01364597]). Outcomes included body weight and body mass index (BMI) over time (z‐score growth curves), and treatment‐emergent adverse events (TEAEs). Previous/ongoing medical conditions that may affect body weight (gastrointestinal and metabolic/nutritional disorders); concomitant antiseizure medications (ASMs) were also evaluated. Results Two hundred nine patients (mean [standard deviation] age 7.9 [4.6] years) were analyzed. Most (154 [73.7%]) had focal‐onset seizures. At study initiation, median (range) BRV dose was 1.0 (0.4–7.5) mg/kg/day. Overall, 189 (90.4%) patients had a previous or ongoing medical condition (gastrointestinal disorders: 43 [20.6%]; metabolism/nutritional disorders: 26 [12.4%]). Most patients followed z‐score curves for body weight and BMI during BRV treatment, although there were outliers in both directions. Incidences of appetite/weight‐change TEAEs were low. Twenty‐three (11.0%) patients had a TEAE of decreased appetite and 14 (6.7%) had a TEAE of weight decreased. Significance Long‐term adjunctive BRV was well tolerated in growing children with no indication of detrimental effects on body weight. Plain Language Summary Brivaracetam is an antiseizure medication (ASM) used to treat seizures in people with epilepsy. Some ASMs can lead to changes in people's appetite and weight. Knowing the effect a drug has on appetite and weight is particularly important in children. We looked at 209 children with epilepsy taking brivaracetam and studied changes in their body weight and body mass index over time. The number of reported side effects related to appetite or weight change was low. There was no apparent long‐term effect on their body weight, even when taking their medical history and use of other ASMs into account.